Mental health: A call to action: Desjarlais, R, Eisenberg, L, Good, B & Kleinman, A (1995) World mental health: Problems and priorities in low-income countries. New York: Oxford University Press. Pp. vii, 382. ISBN 0-19-509540-5 hbk. - Freeman, Melvyn (PINS-Psychology in Society, 2026)
I begin this review of World mental health: Problems and priorities in low-income countries where the book ends, in "A call to action". I do this because this volume is not another academic book on mental health; in its content, its tone and its structure, it is a tool for mobilisation towards better mental health in developing countries. It is not surprising that the authors have launched the book by convening regional conferences and workshops to promote mental health and to facilitate country processes of mental health policy development. This said though, the book is not ·unacademic". The authors are exceptional scholars and this volume is by far the most comprehensive collation of academic material in public mental health yet published. It is clear though that the book has been Mitten to be ·used" rather than merely read.